1991
DOI: 10.1111/j.1471-0528.1991.tb15369.x
|View full text |Cite
|
Sign up to set email alerts
|

The combination of a depot gonadotrophin releasing hormone agonist and cyclical hormone replacement therapy for dysfunctional uterine bleeding

Abstract: Objective— To observe if a combination of a depot GnRH agonist and cyclical hormone replacement therapy decreases menstrual b od loss. Design— open, observational study comparing the objective assessment of menstrual blood loss before, during and after 3 months treatment. Subjects— 20 women with a subjective complaint of heavy menstrual loss in whom no cause could be discovered. Interventions— Each woman received 3 months of depot goserelin (Zoladex) combined with cyclical hormone replacement therapy (Cyclo‐Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Concerns about bone loss and poor tolerability of GnRH agonists have led to a number of studies on estrogen and progestogen ‘addback therapy’ during GnRH agonist treatment. When cyclical estrogen/progestogen hormone replacement therapy has been used in conjunction with GnRH analogs the annoying side‐effects of GnRH agonist treatment are minimized without affecting the control of dysfunctional menstrual bleeding (116).…”
Section: Hormonal Treatments For Menorrhagiamentioning
confidence: 99%
“…Concerns about bone loss and poor tolerability of GnRH agonists have led to a number of studies on estrogen and progestogen ‘addback therapy’ during GnRH agonist treatment. When cyclical estrogen/progestogen hormone replacement therapy has been used in conjunction with GnRH analogs the annoying side‐effects of GnRH agonist treatment are minimized without affecting the control of dysfunctional menstrual bleeding (116).…”
Section: Hormonal Treatments For Menorrhagiamentioning
confidence: 99%
“…Studies in patients with dysfunctional uterine bleeding have shown that symptoms and menorrhagia are reduced by Zoladex treatment but recur after cessation of therapy 7–9 . Patients with polycystic ovary syndrome have demonstrated cyst and serum testosterone reduction 10 .…”
Section: Other Benign Conditionsmentioning
confidence: 99%
“…The addition of HRT means, however, that long‐term treatment is a possibility for young women with recurrent endometriosis, thus avoiding surgery and loss of fertility before pregnancy, when desired, has been attained. The treatment of other menstrual disorders, such as menorrhagia, which cannot always be controlled with current conventional therapy 12 , also becomes a possibility and could avoid the need for hysterectomy and the denial of fertility to young patients. Finally, as GnRH agonists have been shown to reduce fibroid size, such treatment becomes a possibility in young women with fibroids, thus avoiding the need for surgery and loss of fertility.…”
Section: Discussionmentioning
confidence: 99%